Analisis Perbandingan Kinerja Keuangan Bank Syariah Dan Bank Konvensional Di Indonesia Periode 2010-2015 - Wiryanti, Septiana; , Kussudiyarsana S.E., M.Si (2017)
This study aimed to analyze the financial performance perbandingn Islamic Banking and Conventional Banks in Indonesia 2010-2015. The population in this study is the Islamic Banking and Conventional Banks listed on the FSA (Financial Services Authority). Taking a sample of Bank Syariah 5 and 5 samples of conventional banks during the period 2010-2015. Analysis techniques in this study using descriptive statistical analysis and analysis of independent sample t-test. The results of this study indicate that: (1) the ratio of NPLnet and NPLgross of Syariah bank is significantly different from conventional bank, (2) interest rate affects NPLnet and NPLgross conventional bank, (3) exchange rate effect on NPLnet and NPLgross of syariah bank and conventional bank.